2020
DOI: 10.1017/s1368980020001184
|View full text |Cite
|
Sign up to set email alerts
|

The purchase of the Diabetic Healthy Food Basket in Cyprus results in cost savings: is it affordable among the low-income population?

Abstract: Objective: The main objective was to assess the cost, acceptability and affordability of the Cypriot Diabetic Healthy Food Basket (DHFB). Design: The development of DHFB was based on the Cypriot HFB with adjustments based on the nutritional guidelines for diabetes as developed by the American Diabetes Association (ADA) and information retrieved through the questionnaires. Two DHFB were constructed for adult women and adult men (±40 years) diagnosed with diabetes. Affordability was define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…In case of low-adherence to a prescribed diet, patients are likely to experience disease’s relapses, compromising their long-term health [ 26 ]. In contrast, regarding diabetes, the same researchers found that the diabetic nutritional therapy is more affordable compared to other diets such as the healthy diet or the gluten free healthy diet [ 64 ]. Therefore, it could be assumed that not all chronic diseases lead to food insecurity and that each disease may cause different level of food insecurity.…”
Section: Discussionmentioning
confidence: 99%
“…In case of low-adherence to a prescribed diet, patients are likely to experience disease’s relapses, compromising their long-term health [ 26 ]. In contrast, regarding diabetes, the same researchers found that the diabetic nutritional therapy is more affordable compared to other diets such as the healthy diet or the gluten free healthy diet [ 64 ]. Therefore, it could be assumed that not all chronic diseases lead to food insecurity and that each disease may cause different level of food insecurity.…”
Section: Discussionmentioning
confidence: 99%